Effects of insecticide use, host plant resistance, and nitrogen fertilization on the density of Melanaphis sorghi and the production of grain sorghum - Osariyekemwen Uyi; Xinzhi Ni; David Buntin; Michael D. Toews (Scientific Reports)
Abstract Melanaphis sorghi is a serious economically important pest of sorghum, Sorghum bicolor (L.), across the southern USA. Therefore, developing and refining integrated strategies that provide effective control is key to the management of this pest. The current study examined the influence of nitrogen (N) fertilization, sorghum cultivar and insecticide applications on M. sorghi and grain sorghum yield at Tifton, Georgia (31.5120° N, 83.6434° W). Field trials with three insecticide treatments (untreated control, flupyradifurone in-furrow at 117 g/ha, and flupyradifurone foliar at 73 g/ha), three nitrogen fertilization rates (25, 50 and 100 kg/ha) and two sorghum cultivars (resistant: DKS37-07 and susceptible: DKS53-53) were conducted on grain sorghum in the spring/summer of 2022 and 2023. Compared to the medium N fertilization, Low and high N fertilization supported higher aphid density and severity of infestation (cumulative insect days [CID]) on both the susceptible and resistant cultivars for both 2022 and 2023. Aphid density and severity of infestation on the susceptible sorghum cultivar (DKS53-53) were 3.4–4.8-fold greater than on the resistant cultivar (DKS37-07) for both low and high N fertilization plots in 2022. While a single foliar and in-furrow insecticide application significantly reduced infestations below the economic threshold across all treatment combinations in 2022, aphid populations were too low to warrant foliar application in 2023. Nitrogen fertilization was associated with improved yield as the high N fertilization preserved yield for both sorghum cultivars. Compared to untreated plots, in-furrow and foliar insecticide applications supported greater grain sorghum yield across all insecticide treatments only in 2022. The study suggests that manipulating N fertilization, utilizing resistant sorghum cultivars and in-furrow and foliar insecticide application can synergistically suppress aphid infestations and improve grain yield in sorghum production in southern USA.